CERS4 predicts positive anti-PD-1 response and promotes immunomodulation through Rhob-mediated suppression of CD8+Tim3+ exhausted T cells in non-small cell lung cancer - Jian Wang; Run-Ze Li; Wen-Jun Wang; Hu-Dan Pan; Chun Xie; Lee-Fong Yau; Xing-Xia Wang; Wei-Li Long; Rui-Hong Chen; Tu-Liang Liang; Lin-Rui Ma; Jia-Xin Li; et al. (Elsevier, 2023)
Non-small cell lung cancer (NSCLC) is one of the main malignant tumors with high mortality and short survival time. Immunotherapy has become the standard treatment for advanced NSCLC, but it has the problems of drug resistance and low response rate. Therefore, obtaining effective biomarkers to predict and enhance immune checkpoint inhibitors (ICIs) efficacy in NSCLC is important. Sphingolipid metabolism is recently found to be closely involved in tumor immunotherapy. CERS4, an important sphingolipid metabolizing enzyme, is positively correlated with the efficacy of anti-PD-1 therapy for NSCLC. Upregulation of CERS4 expression could improve the efficacy of anti-PD-1 therapy for NSCLC. High expression of CERS4 could downregulate the expression of Rhob in tumor. Significantly, the ratio of CD4+/CD8+ T cell increased and the ratio of Tim-3+/CD8+ T cell decreased in spleen and peripheral blood cells. When Rhob was knocked out, the efficacy of PD-1 mAb treatment increased, and the frequency of Tim-3+ CD8+ T cell decreased. This finding further confirmed the role of sphingolipid metabolites in regulating the immunotherapeutic function of NSCLC. These metabolites may improve the efficacy of PD-1 mAb in NSCLC by regulating the CERS4/Rhob/Tim-3 axis. Overall, this study provided a potential and effective target for predicting and improving the efficacy of ICIs for NSCLC. It also provided a new perspective for the study on the mechanisms of ICIs resistance for NSCLC.